Design of software-defined radio transmitter sytems - Han, Zhaoxu (Nanyang Technological University, 2024)
With the development of IoT technology and smart devices, the demands for transmitting multiple parameter-configurable wideband signals is increasing rapidly. Nowadays, traditional 3G technology can no longer meet high frequency communication demands. 4G and 5G technology also need to be improved and optimized because of problems with signal attenuation and so on. The design of the next-generation radio transmitter can rely on software-defined technologies, specifically Software-Defined Radio. By integrating Massive MIMO (Multiple-Input Multiple-Output) and other related technologies, and incorporating advanced design theories, a software-defined radio transmitter circuit can be developed to meet modern usage requirements. This dissertation centers on the design and implementation of a Software Defined Radio (SDR) transmitter system, in order to meet the demands for wideband signal transmission and reception, as well as achieving stable operation in high-frequency bands. The design incorporates essential modules, including the RF front-end circuit, analog-to-digital and digital-to-analog conversion circuits, and RF switch circuits. Through meticulous design, the system ensures stability and reliability across an extensive frequency range. During testing, a comprehensive verification and analysis of the individual blocks performance of the software-defined radio transmitter was presented. The testing items are based on the HackRF One platform, utilizing the connection ports of HackRF One to interface with core components such as the microcontroller for debugging instruction input. The test signals are modulated using the SDRangel host platform. Due to the limitations of the internal structure of HackRF One and the restrictions on the precision and variety of instruments required during the testing phase, many idealized factors were introduced into the test results. Additionally, the accuracy testing was only completed for the 4.9 GHz validation. It is hoped that suitable testing solutions can be identified in future research to enhance this aspect. Nevertheless, this design still holds significant reference value, as the circuit structures described are typical of RF front-end and control architectures, serving as a foundation for future developments in the field of radio frequency.